Transmission dynamics and timing of key events for SARS-CoV-2 infection in healthcare workers. Issue 7 (3rd July 2021) - Emecen, Ahmet Naci; Basoglu Sensoy, Ecem; Sezgin, Edanur; Yildirim Ustuner, Buket; Keskin, Salih; Siyve, Neslisah; Celik, Saadet Goksu; Bayrak, Gamze; Senturk Durukan, Nurcan; Coskun Beyan, Ayse; Ergor, Alp; Unal, Belgin; et al.
Abstract: Background: Healthcare workers (HCWs) have increased risk for SARS-CoV-2 infection via contacts in hospitals, as well as via transmission in the community. Serial interval, which is defined as the time between symptom onsets in an infector–infectee pair, and the incubation period are key parameters in determining the control strategies for COVID-19. This study aimed to evaluate surveillance of HCWs and estimate the serial interval and incubation period of COVID-19. Methods: A total of 149 HCWs and 36 certain infector–infectee pairs between 19th March 2020 and 1st November 2020 in a university hospital were included in the study. Epidemiological characteristics were recorded. Serial interval and incubation period were estimated using parametric accelerated failure time models. Results: Forty HCWs (26.8%) were detected via contact-based surveillance. Of 100 HCWs epidemiologically linked with a confirmed COVID-19 case, 36 (36%) had contact with a colleague. The median serial interval was 3.93 days (95% CI: 3.17–4.83). Of symptomatic HCWs, 97.5% had developed symptoms 13.71 (95% CI: 9.39–18.73) days after symptom onset of the primary case. The median incubation period was 3.99 (95% CI: 3.25–4.84) days. Of symptomatic HCWs, 97.5% developed symptoms within 9.49 (95% CI: 6.75–12.20) days after infection. Conclusions: The serial interval and the incubation period of COVID-19 in HCWs were shorter than in the general population. Rigorous contact tracing and isolation of infected HCWs could have resulted in shorter serial intervals. Implementation of more stringent in-hospital control measures focussed on transmission between HCWs should be considered.